Orbital fat Augmentation in volumetric upper eyelid fold rejuvenation - Elhamaky, Tarek (Aesthetic Medicine, 2025)
Purpose: to investigate the efficacy of adjunctive orbital fat flap and/or graft to eyelid crease forming sutures in upper eyelid fold rejuvenation. Methods: this prospective study included 24 patients (43 eyelids) who underwent orbital fat augmentation with crease-forming sutures. All patients underwent an eyelid crease evaluation and patient satisfaction evaluation at baseline, 2 weeks and 6 months after the surgery. Results: at the 6-month follow-up, the eyelid crease height significantly decreased from 12.4± 0.48 to 8.2± 0.4 mm, the mean baseline upper lid fold significantly increased from 19.1± 0.6 to 21.5± 1mm, the mean baseline pretarsal space (PTS) significantly decreased from 7.8± 0.74 to 4.6± 0.45 mm. Volumetric eyelid fold augmentation was achieved through preaponeurotic fat flap, nasal fat flap, nasal fat graft and mixed augmentation in 11, 9, 10, and 13 eyelids, respectively. Baseline lid crease symmetry was graded as moderate asymmetry in 15 (62.5%) patients and obvious asymmetry in 9 (37.5%) patients. At the 6-month follow-up, symmetry improved, with 21 (87.5%) patients showing symmetry or mild asymmetry and only 3 (12.5%) patients exhibiting mild asymmetry. At the 6-month follow-up, GAIS scores of 1,2, and 3 were observed in 3 (12.5%), 19 (79.2%), and 2 (8.3 %) patients. The mean baseline BOE increased significantly from 42.5±3.9 points to 85.5±4.6 points over the same period. Conclusions: our cohort shows favorable cosmetic results and patient satisfaction in the treatment of high eyelid creases with minimal risks.